Hydrochloric Acid and/or Sodium Hydroxide-modified Zeolite Y for Catalytic Hydrotreating of α-Cellulose Bio-Oil - Jason Mandela; Wega Trisunaryanti; Triyono Triyono; Mamoru Koketsu; Dyah Ayu Fatmawati (Indonesian Journal of Chemistry, 2021)
The zeolite Y had been successfully modified by HCl and/or NaOH treatment. The modification of zeolite Y was performed by leaching the protonated zeolite Y (HY) in HCl solution (0.1 and 0.5 M) at 70 °C for 3 h resulting in DY0.1 and DY0.5. Subsequently, HY, DY0.1, and DY0.5 zeolites were immersed in 0.1 M NaOH for 15 min at room temperature resulting in AHY, ADY0.1, and ADY0.5. All samples were analyzed for acidity, crystallinity, Si/Al ratio, morphology, and textural properties. The catalytic performance of all samples was investigated in hydrotreating of α-cellulose bio-oil with a catalyst/feed weight ratio of 1/30. The HCl and NaOH treatment led to the decrease of the zeolite Y crystallinity and the increase of the zeolite Y average pore diameter (i.e., the mesopore distribution). The ADY0.5 gave the highest mesopore distribution, which was 43.7%, with an average pore diameter of 4.59 nm. Moreover, both of the treatments were found to increase the Si/Al ratio that caused the decrease of zeolites Y acidity. All the zeolite Y samples gave better catalytic activity to produce liquid products after being treated by NaOH. The sample ADY0.5 managed to produce 6.12% of 1-isopropyl-2,4-dimethylbenzene that has good potential to be processed into fuel.